ANALISIS REAKSI PASAR MODAL TERHADAP PENGUMUMAN KENAIKAN HARGA BBM PADA 3 SEPTEMBER 2022 - Anggriawan, Bayu; Candradewi, Ni Made Reina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
Capital Market Efficiecy is a concept that aims to identify the market reaction to informations that contained in an event. This research aims to determine capital market reaction to the announcement of increasing fuel prices that happened on September, 3, 2022. There are 2 (two) variables that used in this research, namely average abnormal return dan average trading volume activity. This research is conducted on companies that are listed in the Transportation and Logistics Sector (IDXTRANS) on Indonesia Stock Market. The number of samples that used in this research are 22 companies which selected using purposive sampling. This research uses One Sample T-test and One Sample Wilcoxon Signed Rank Test as data analysis techniques. The result of this research is that there were significant average abnormal return and average trading volume activity around the event period, so this indicate that the announcement of increasing fuel price on September 3, 2022 had information that could give reaction to the market.